Peluang Usaha Dalam Pemanfaatan Sampah Untuk Meningkatkan Ekonomi Keluarga - Entaresmen, Raden Ajeng; Firdayetti, Firdayetti; Lutfi, Muhammad Yudhi; Agustina, Rizka; Ata, Muhammad (Jurnal Pengabdian Masyarakat Akademisi, 2026)
This Community Service Program aims to enhance community knowledge, skills, and entrepreneurial capacity in utilizing waste as a business opportunity to improve family economic conditions. The program was implemented using an educational approach through counseling and training activities, covering concepts of waste utilization, waste-based business opportunities, waste bank management, and basic business planning and marketing strategies. The activities were carried out through several stages, including preparation, implementation of counseling and training sessions, and evaluation. The target participants were residents of the Puri Hutama Housing Complex, particularly housewives and productive community members as prospective entrepreneurs. The results indicate an improvement in participants’ understanding of the importance of waste segregation and the economic potential of waste management. Participants were able to identify waste-based business ideas, understand simple production processes, and develop initial business plans oriented toward sustainability. Furthermore, the program encouraged active community participation in waste bank management as a means of family economic empowerment. The outputs of the program include increased entrepreneurial capacity of the community, waste-based business plans, and contributions to the achievement of higher education Key Performance Indicators (KPIs). Overall, this community service activity supports sustainable environmental management while simultaneously strengthening family economic empowerment through waste utilization.